Food Safety and Waste Management Practices Among Canteen Operators of Schools and Colleges: Cauayan City, Isabela - Antalan, Mila F.; Tungpalan, Krichelle A. (International Journal of Psychosocial Rehabilitation, 2020)
College and university food service operations are great contributors of food waste, and such a suggestions of food recycling such as composting, donation of food to local food banks, or sale of food waste to farmers for animal feedings to minimize food expenditures (Ju, S., et. al. (2016). Hence, this study aimed to examine the foodservice administrators’ food waste management practices among canteen operators of educational institutions of Cauayan City, Isabela. In this study, the research method used was the descriptive method. Survey Questionnaire was used to gather data needed to assess the present condition of canteen operators in terms of food safety and how they manage their solid wastes. Some statistical tools were applied to interpret and analyzed data collected. It was found out that canteen operators have their own design of protecting foods and ways of maintaining the cleanliness and sanitation of their surroundings.